4. Migracja zarobkowa z Kirgistanu Znaczenie gospodarcze i polityczne kirgiskich gastarbaiterów .......... 143 - Polit, Konstancja (Kirgistan – oblicza transformacji, 2020)
LABOUR MIGRATION FROM KYRGYZSTAN – THE ECONOMIC AND POLITICAL IMPORTANCE OF KYRGYZ „GASTARBEITERS” Labour migration from Kyrgyzstan, a country troubled with chronic unemployment, poverty and demographic explosion is a very specific phenomenon. In 2017 the number of emigrants probably reached 800,000 (1/8 of the population); 80% of them chose Russia. That year remittances accounted for 34% of GDP. Additionally, emigration helps reduce unemployment and social tensions. However, because of its dependence on Russia, Kyrgyzstan, with its little oil and gas resources, became almost pathologically dependent on prices of hydrocarbons. Young, resourceful and educated people are leaving the country whereas the government, having only temporary control over the economy, is putting off the necessary reforms ad infinitum.